Improving the Quality of Life of Patients with Arterial Hypertension in Diabetes Mellitus - Kirgizbayeva Aray ,; Umbetyarova Lyzzat ,; Bissenbina Gulzhakan ,; Yessergeneva Riza ,; S.A. Mankibaeva ,; S.N. Abdureshov, (Journal of Pharmacy and Nutrition Sciences, 2019)
Currently, there are no recommendations on the features of detecting early signs of CHF in patients with diabetes mellitus. And they are necessary, taking into account that in case of diabetes mellitus type 2 (more than 95% of all patients with diabetes mellitus), the overwhelming number of patients are overweight and obesity, which can affect the validity of the 6-minute walk test and scale clinical state assessment (SHOX) in the modification. In the treatment of patients with CHF, the “gold” standard is the use of angiotensin-converting enzyme inhibitors (ACE inhibitors) according to the third edition of the recommendations on the diagnosis and treatment of CHF. Antagonists of receptors for angiotensin II type 1 (APA II) remain at the same time reserve drugs. Adherence to these standards of patients in different regions of the Russian Federation varies over a rather wide range, and there is almost no information about the compliance of patients with diabetes mellitus with prescribed drug therapy in the presence of CHF. Thus, the need to identify the frequency of CHF in patients with type 2 diabetes, clarifying the features of this diagnosis and optimizing the treatment of such patients is beyond doubt. Objective: to clarify the frequency of chronic heart failure in patients with type 2 diabetes in the specialized | department of the hospital and unorganized urban population, to assess the adequacy of its diagnosis and treatment. Research Objectives: Identify the prevalence of chronic heart failure in patients with type 2 diabetes. To assess the level of diagnosis of chronic heart failure in patients with type 2 diabetes. To analyze the state of drug therapy for patients with type 2 diabetes in the presence of chronic serum